Sexual behaviour of in-school adolescents in Ibadan, South-West Nigeria (2008)
This study was a crossectional survey conducted among 716 senior secondary school adolescents in Ibadan from March to August 2005. The result of 695 that was analyzed revealed that the mean age of 15±2.6years. 28.3% of the respondents had previous sexual exposure with higher proportions being male (p=0.00043). Majorities’ first sexual exposure was unplanned. Family settings and educational level do not have significant influence on the previous sexual exposure. The methods of sexual activity were mainly through vagina route while some had also practiced oral and anal sex. Most of those that are sexually exposed had more than one partner. About half of the respondents learn about sex from their friends while others through their parents and media. We conclude that in-school adolescents practiced unsafe sexual activity and they are therefore predisposed to STI/HIV and other reproductive health risks